2016
DOI: 10.1016/j.oceaneng.2015.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Direct simulation and experimental study of zigzag maneuver of KCS in shallow water

Abstract: The KCS container ship on a zigzag maneuver in shallow water is studied experimentally and numerically. The approach conditions are and. Experiments were performed in the shallow water towing tank at Flanders Hydraulics Research for the workshop on verification and validation of ship manoeuvring simulation methods SIMMAN 2014. CFD simulations were initially performed blind at the nominal rudder rate of 16.8 deg/s using direct discretization of moving rudder and propeller, including the tank bottom but neglecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(22 citation statements)
references
References 16 publications
0
22
0
Order By: Relevance
“…CFD has been enhanced significantly in recent years and numerous studies have been presented for steady problems such as resistance and stationary manoeuvres. Only recently, CFD studies have addressed the problem of non-steady conditions such as direct manoeuvring simulation in calm water (see Carrica et al (2012), Carrica et al (2016)) and tests in oblique waves (see Akimoto (2010)). It is obvious that manoeuvring in waves is a more time and resources demanding problem because of its complex nature.…”
Section: Review Of Proposed Methods To Simulate Manoeuvring In Wavesmentioning
confidence: 99%
“…CFD has been enhanced significantly in recent years and numerous studies have been presented for steady problems such as resistance and stationary manoeuvres. Only recently, CFD studies have addressed the problem of non-steady conditions such as direct manoeuvring simulation in calm water (see Carrica et al (2012), Carrica et al (2016)) and tests in oblique waves (see Akimoto (2010)). It is obvious that manoeuvring in waves is a more time and resources demanding problem because of its complex nature.…”
Section: Review Of Proposed Methods To Simulate Manoeuvring In Wavesmentioning
confidence: 99%
“…Many experimental and numerical investigations have explored the changes to the vortex system for varying angles of oblique flow, where again the flow angles considered are generally larger than would be considered operational leeway angles for a wind-assisted ship. From the oil film experiments of [6], to detailed measurements of the vortex wake by [30], to state-of-the-art numerical work such as the detached-eddy Reynolds-averaged Navier-Stokes simulations by Carrica et al [7], Abdel-Maksoud et al [1], and Xing, Bhushan, and Stern [47], the flow patterns have been well documented. As described by [30], the topology for the wake of a ship sailing with a leeway angle is characterized by several vortices, of which the forebody keel vortex (FKV), forebody bilge vortex (FBV), and forebody side vortex (FSV) are relevant here.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…The sinkage fluctuates during the travel of the vessel. As mentioned before, due to the limitation of the test facility, the experiments carried out by Duffy [17] only performed 5 L pp after the step bank. However, in the present study, it is showed that a more critical peak has occurred when the vessel travelled 12 L pp after the step bank.…”
Section: Total Resistance Drag Force and Sinkagementioning
confidence: 99%
“…The method was further expanded and used for simulating ship self-propulsion [14], manoeuvring [15] as well as dynamic stability [16]. Based on the works listed above, Carrica et al [17] also experimentally and numerically investigate the 20/5 zigzag manoeuvre for the container ship KCS in shallow water.…”
Section: Introductionmentioning
confidence: 99%